Recent advances in low-carbon belitic calcium sulfoaluminate (BCSA) cement and concrete for rapid infrastructure rehabilitation and repair - Bescher Eric (MATEC Web of Conferences)
The development of sustainable, high-performance cementitious materials for infrastructure rehabilitation presents not only technical but also institutional and regulatory challenges. Belitic calcium sulfoaluminate (BCSA) cement—first developed in the United States in the 1970s—has emerged as a promising low-carbon alternative, especially in applications requiring rapid strength gain. This presentation reviews recent progress in BCSA cement technology, examines some of its performance characteristics and environmental benefits, and explores its synergistic potential as an early-strength enhancer in widely adopted low-carbon cements such as Portland-limestone cement (PLC) and limestone-calcined clay cement (LC3.